Developing employability in higher education music - Bennett, Dawn (Sage Publications, 2016)
The development of employability in higher music education concerns students, musicians, educators, administrators and funding bodies, and yet employability is both impossible to measure and poorly defined. This paper sets the context for a set of short papers that explore employability from the perspective of music. Because many of the issues they raise have relevance across the creative industries, this paper discusses research that positions them within this broader context. The paper highlights the need for both the functional (how-to) aspects of employability and those that are cognitive: development of students' cognitive dispositions and their capacity to engage as professionals. As such, the paper argues that employability requires collaborative action on three fronts: enhancement of the ways in which employment outcomes are defined and measured; initiatives that engage students in career- and life-relevant activities; and advocacy work that re-aligns stakeholder perceptions of graduate work and employability itself.